Dainavà. Vardo reikšmė, istorija ir kilmė - Karaliūnas, Simas (Baltistica, 2006)
Dainavà. MEANING, HISTORY AND ORIGIN OF THE NAME Several villages in Southern Lithuania bear the name Dainavà (acc. sg. Daĩnavą). There is a village of this name, inhabitated by the Lithuanians, also in Byelorussia, in Grodno region, Zietela district (in Byelorussian Dziatlovo as well as Diatlovo). The name is attested in 13th c. historical sources written in Latin: Deynowe, Denowe. In 16th c. Russian chronicles we find Doinova (Дойнова). It has been long ago assumed by investigators that this was the Lithuanian name for the Yatvingians, a tribe of the Western Balts. In addition to this, there are ten villages in Aukštaičiai (in the Highlands of Lithuania) called Dainiaĩ. It was suggested by historians that in some cases these villages got the name from the name plur. *dainiaĩ (sg. *dainỹs) of the population of the Dainava region. In Lithuanian there are adjectives dienì and dienė̃ „pregnant, with calf, in foal” (< *dēin(i)i̯o-), used, e. g., in dienì kárvė „cow, that calves“, dienì kumẽlė „mare in foal“. Lith. diẽndaržis „cattleyard; enclosure“ etymologically correspond to Latv. dìendā̀rzs, dìendā̀rzs2, diendaržis „cattlehurdle“. They are compounds that contain Baltic * diena, *diene (acc. sg. *diẽną, *diẽnę) subst. fem. „cow“ and Lith. dar̃žas, Latv. dā̀rzs „kitchen-garden“. It is possible to reconstruct East Baltic * diena, * diene (acc. sg. * diẽną, *diẽnę) subst. fem. „cow“ which derive from Protobaltic nouns *dḗinā, *dḗinē subst. fem. „cow“. In the East Latvian dialects we found atdiẽne „a cow, that calves in the second year“, adaine, a[t]daîne „a cow, that calves in the second year“, which contain a prefix at- and Baltic *diena, *diene subst. fem. „cow“ respectively *dā́inē „cow“. OInd. dhenúḥ fem. „(milk) cow; female“, Avesta daēnu- fem. „female“, u stem, OInd. dhénā fem. „female; milk-cow; brests“, ā stem, seem to be etymological cognates of these Baltic words. So there are good grounds for believing that the name of the inhabitants of the former region Dainava pl. * dainiaĩ (sg. *dainỹs, acc. sg. *dáinin < *dāinin) with a primitive meaning „cow-herds, cow-boys“ in historical-comparative aspect is connected with *dā́inē „cow“. From the very outset, the name pl. *dainiaĩ with the suffix *-(i)i̯o- evidently must have meant tribesmen as countable members of a tribe. Dainavà, Dainuvà, derivatives with the suffixes –ava/-uva, might have been collective names for the ethnic group as an indivisible whole. It seems that the names Dainavà, Dainuvà have etymologically nothing to do with the hydronyms Dainavà Daĩn-upis etc., as has been assumed by some scholars, then they may represent quite a different root. They are most likely derived with a suffix -n- from the root *deih1- „spank along, dash, speed along; turn, go round“, which is attested in Latv. diêt (deju) „to dance; to jump (about), leap; to sing“, OInd. dī́yati „he flies, soars“, Gr. δινέω, δινεύω „to turn, twist, swing...“.